The National Italian Guidelines on the diagnosis and treatment of children with pediatric ataxias - Lacorte, Eleonora; Piscopo, Paola; Sagliocca, Luciano; Vignatelli, Luca; Taruscio, Domenica; Vanacore, Nicola; , The Ataxia Guideline Development Working Group (GDWG); Bacigalupo, I; Beccani, L; Bellomo, G; Bertini, E; Biagiotti, S; et al. (Frontiers in Neurology, 2022)
Background Ataxia is a rare neurological condition causing a deficit in the coordination of motor activities, preventing the fluidity of movements. Children with ataxia may show several different ataxic signs, along with difficulties in walking autonomously and ataxic gait often associated with trunk instability. Ataxic signs can be either acute or chronic, and in either case, the diagnosis can be extremely complex. Symptoms and their etiology are often widely heterogeneous, even within the same condition. Methods The guideline was developed based on the methodology defined by the Methodological Handbook of the Italian National Guideline System (SNLG) and was reported following the AGREE-II checklist. The SNLG methodology required the adoption of the GRADE approach for the whole development process. To facilitate the implementation of the contents and recommendations from the guideline, two care pathways were developed based on the NICE and the European Pathway Association (EPA) models. Results The guideline included 28 clinical questions, 4 on the identification and management of acute ataxias, and 24 on the diagnosis and management of chronic ataxias. The document included 44 recommendations, 37 clinical recommendations, and 7 recommendations for research. Conclusion The working group, despite the lack and methodological limitations of the evidence, deemed as essential to provide indications and recommendations, in particular in some clinically relevant areas. The care pathway was produced as a tool to facilitate the implementation of the contents and recommendations. The interactive version of the pathway is available on the SNLG website along with a leaflet dedicated to families and caregivers.